Large–scale genetic analysis and biological traits of two SigB factors in Listeria monocytogenes: lineage correlations and differential functions - Pan Mao; Yan Wang; Lin Gan; Lingyun Liu; Jinni Chen; Lingling Li; Hui Sun; Xia Luo; Changyun Ye (Frontiers in Microbiology, 2023)
IntroductionListeria monocytogenes is a globally distributed bacterium that exhibits genetic diversity and trait heterogeneity. The alternative sigma factor SigB serves as a crucial transcriptional regulator essential for responding to environmental stress conditions and facilitating host infection.MethodWe employed a comprehensive genetic analysis of sigB in a dataset comprising 46,921 L. monocytogenes genomes. The functional attributes of SigB were evaluated by phenotypic experiments.ResultsOur study revealed the presence of two predominant SigB factors (SigBT1 and SigBT2) in L. monocytogenes, with a robust correlation between SigBT1 and lineages I and III, as well as SigBT2 and lineage II. Furthermore, SigBT1 exhibits superior performance in promoting cellular invasion, cytotoxicity and enhancing biofilm formation and cold tolerance abilities under minimally defined media conditions compared to SigBT2.DiscussionThe functional characteristics of SigBT1 suggest a potential association with the epidemiology of lineages I and III strains in both human hosts and the natural environment. Our findings highlight the important role of distinct SigB factors in influencing the biological traits of L. monocytogenes of different lineages, thus highlighting its distinct pathogenic and adaptive attributes.